Метрологічне забезпечення вимірювання вмісту загального органічного вуглецю у мінеральних водах - Кисилевська, Альона; Коєва, Христина; Тонкус, Олексій (Видавництво Львівської політехніки, 2016)
Розкрито сутність метрологічного забезпечення визначення органічного вуглецю в мінеральних водах. Проведено аналітичний огляд відомих методів та засобів метрологічного забезпечення визначення загального органічного вуглецю в мінеральних водах. Детально розглянуто конструкцію, технічні вимоги та принцип роботи аналізатора загального органічного вуглецю ТОС-V фірми “Shimadzu”. Виконано розрахунки щодо визначення міжкалібрувальних інтервалів приладу. Окреслено основні переваги методу інфрачервоної спектрометрії. Наведено дані щодо валідації методики, розраховано основні метрологічні характеристики. Побудовано контрольну карту Шухарта. Раскрыта сущность метрологического обеспечения определения органического углерода в минеральных водах. Проведен аналитический обзор известных методов и средств метрологического обеспечения определения общего органического углерода в минеральных водах. Детально рассмотрены конструкция, технические требования и принцип работы анализатора общего органического углерода ТОС-V фирмы “Shimadzu”. Выполнены расчеты по определению межкалибровочных интервалов прибора. Определены основные преимущества метода инфракрасной спектрометрии. Приведены данные по валидации методики, рассчитаны основные метрологические характеристики. Построена контрольная карта Шухарта. The studying and standardization of the mineral waters requires mandatory content control of their chemical indexes. Nearby with the dissolve salts there are always exist the organic substances. The mineral waters with high organic substances (Corg, total organic carbon no less than 5,0 mg/l) are used for treating the hepatobiliary system deceases, urinary tracts deceases, and genital and metabolism disturbances. The researches of safety and quality of the mineral waters relate to the area of the state`s metrological control and supervision. The pledge of adequate assessment of the organic substances content is proper metrological provision, the analysis of the reasons that caused an error, the comparison of reliability criteria and accuracy of the analysis methods. Among the number of the methods of measurement the organic substances content in the mineral waters most of which are durable and are not precise are distinguished the infrared spectrometry method. The methods provides the acid analyzer usage, whose working principle is based on high-temperature catalytic carbon compounds oxidation in the water sample till carbon oxide hereinafter its determination in usage as ultra-red rays detector or flame-ionization detector. There was considered in the article the principle of TOC-V analyzer construction action that belongs to “Shimadzu” company (Japanese). It was calculated calibration interval for this device. According to the calculations of the laboratory, that exploits it, this interval varies in one year. It was also assessed the validation characteristics of the methods of the total carbon determination with the infrared spectrometry method for the mineral waters by means of the total organic carbon analyzer TOC –V “Shimadzu” company. It was presented in the article the data on the subject of the methods of measurement total organic carbon validation. The methods validation is necessary for persuasion until the beginning of its usage, that the results, that are got by means of usage of this methods, satisfy the goals that have been established. Besides this, the validation enables to: cut down the quantity of mistakes during the methods usage, detect and correct the methods gaps on the nascent states, optimize and determine the operational characteristics, process and confirm the equation for determine the result, invite other test laboratories, that will be able to escalate the confidence in the methods. The laboratory has to make sure that the methods can be used in the proper way, to achieve the conformity the operational characteristics, that have been established and to get satisfactory results. In the test laboratory that has been given at the validation of previously mentioned methods is conducted the evaluation of results precision. It was conducted ten similar measurements the index contest (standard sample 200 mg/l), it was also calculated the precision. The standard deflection is 0,56 mg/l, relative – 0, 28%. The convergence – 1,57. As a control tool of stability the results, the Shuhard`s controlled cards were used. Therefore, the determination of organic carbon in the mineral waters is an integral part of their quality monitoring. There was disclosed in the article the sense of metrological provision for identifying the organic carbon in the mineral waters and it was evaluated the validation characteristics of the determinative methods of the total organic carbon by the infrared spectrometry method for the mineral waters by the means of TOC-V analyzer that belongs to “Shimadzu” company. The validate researches that have been conducted, showed that the methods is characterized as a rather selective, repeatable and precise and may be recommended for using in any test laboratory, which conducts the researches to determine the organic substances consent in the mineral waters.
Keywords: метрологічне забезпечення; загальний органічний вуглець; мінеральні води; метрологическое обеспечение; общий органический углерод; минеральные воды; metrological support; total organic carbon; mineral waters; 006.91:543.37.6:615.327